Successful Reversal of Chronic Incapacitating Post-TIPS Encephalopathy by Balloon Occlusion of the Stent - Daphna Fenyves; Michel P Dufresne; Jean Raymond; Michel Lafortune; Bernard Willems; Gilles Pomier-Layrargues (Canadian Journal of Gastroenterology)
Transjugular intrahepatic portosystemic shunt (TIPS) placement is a new technique allowing decompression of the portal system without the need for abdominal surgery or general anesthetic. This promising procedure appears safe, and is being evaluated in the context of life threatening uncontrollable variceal hemorrhage as well as ascites refractory to medical treatment. Following TIPS, portal flow diversion is associated with hepatic encephalopathy in up to 25% of patients. This is most often mild and treatable but may become uncontrollable, incapacitating and even life threatening in up to 3 to 5% of cases. The authors present two patients in whom such life threatening encephalopathy and stupor was reversed by transjugular balloon occlusion of the TIPS.